A multimodal pilot study of default mode network (DMN) connectivity across the lifespan in healthy volunteers using functional imaging, CSF, and plasma Alzheimer's disease biomarkers. (20th December 2022) - Shapiro, Noah L; Galler, Jake A; Trombetta, Bianca A.; LaCasse, Kathryn; Ramirez, Christopher E.; Riley, Misha M.; Williams, Victoria J.; Kivisäkk, Pia; Salat, David H; Rashid, Barnaly; Arnold, Steven E.
Abstract: Background: Normal aging is associated with decreased functional connectivity (FC) in the brain's default mode network (DMN). Additionally, cerebral burden of both amyloid‐β (Aβ) and tau proteins further contribute to decreased DMN FC in the course of the normal aging process (Wales and Leung, 2021). However, the current literature is sparse and unclear as to the independent actions of Aβand tau on FC of DMN, with tau being associated with general hypoconnectivity (Wales and Leung, 2021). The current pilot study examines resting state fMRI (rsfMRI) data in conjunction with Alzheimer's Amyloid/Tau/Neurodegeneration (ATN) biofluid biomarkers in healthy individuals, using the isthmus cingulate of the retrosplenial cortex as seed for FC analysis of the DMN. Method: rsfMRI scans are collected in the LifeSPAN Biobanking project [ongoing]. Scans are preprocessed utilizing standard FreeSurfer pipeline. Standard parcellations are assigned using the Desikan‐Killiany atlas. In initial analyses, isthmus cingulate served as the seed for DMN analysis using the FSFAST processing stream within FreeSurfer. ATN biomarkers are obtained from cerebrospinal fluid (CSF) and the following biomarker ratios were computed: Aβ42 /Aβ40 (Aβ ratio) and phosphorylated tau‐181 (pTau181) / total Tau (tTau) (pTau181/tTau ratio). Result: In the initial 14 participants (aged 26‐82 years) [Table 1], General Linear Models (GLMs), adjusted for age, were utilized to evaluate the associations between DMN FC and the following AD biomarkers: Aβ40, Aβ42, Aβ ratio, tTau, pTau181, and pTau181/tTau ratio [Table 2; Figure 1]. After correcting for multiple comparisons (p<0.05), significant association between tTau, and the FC between the DMN and the right inferior temporal region was observed [Table 3]. Conclusion: The pilot analysis indicates at least tTau has an association with DMN FC, but sample size precludes conclusion or interpretation. Preliminary data obtained in this exploratory analysis provides a framework for examining the effect of AD biomarkers on the DMN and other functional networks. Future research will incorporate synaptic, inflammatory and other markers into similar statistical models and report preliminary associations. Reference Wales R, Leung H‐C. The Effects of Amyloid and Tau on Functional Network Connectivity in Older Populations. Brain. 2021;142(8):2483‐2491. doi:10.1093/brain/awz162